Investigating the economic and environmental impacts of a technological shift towards hydrogen-based solutions for steel manufacture in high-renewable electricity mix scenarios for Italy. Issue 1 (1st November 2022) - Conte, Marco; Rinaldi, Lorenzo; Tonini, Francesco; Fumagalli, Tommaso; Lorenzin, Giacomo; Piras, Paolo; Sommariva, Gian Giacomo; Rocco, Matteo Vincenzo; Colombo, Emanuela
Abstract: Steel production is one of the most carbon-intensive industrial sectors, responsible for 8% of European CO2 emissions. While traditional furnaces strongly rely on the consumption of coal or natural gas, potential opportunities for decarbonization stand in the adoption of alternative technologies such as hydrogen-based Direct Reduction Iron (DRI) coupled with Electric Arc Furnaces (EAF). This work focuses on the Italian steel sector and aims at assessing the potential economic and environmental impact of a switch towards such hydrogen-based technology. Three scenarios have been analyzed, all of which are grounded on the common assumption that hydrogen is produced by employing electrolyzers purchasing electricity from the grid. In the first scenario, the share of electricity production from renewable sources (RES) in the national electricity mix coincides with the one in the current Italian situation. The second scenario reflects the national target of 55% of electricity generated by low-carbon technologies. In the last scenario, the RES share in the electricity mix is 100%, meaning steel production plants are fully supplied with green hydrogen. The analysis is carried out by adopting a multi-regional input-output model for sectorial LCA, which allows to highlight the interlinkages of the steel industry with other sectors in different regional areas. The results show that a switch to DRI with EAF technology, coupled with the increase of RES penetration, allows to reduce the CO2 emissions of the Italian steel sector up to 14%, leading to an increase in employment of about 12 thousand units. It is also worth noting that a larger penetration of electricity produced from RES, which are mostly local, would be a significant improvement in terms of energy security of the steel sector, lowering its dependence on foreign fossil resources.